Activity of the Summer Party of the 18th Japanese Antarctic Research Expedition in 1976-1977 - Susumu KOKUBUN (National Institute of Polar Research, 1978)
Summer operations of the 18th Japanese Antarctic Research Expedition (JARE-18) are outlined, with a brief description of the expedition mission. The icebreaker FUJI, carrying 500 tons of cargo and equipped with three helicopters and an airplane, Cessna F185, left Tokyo on November 25, 1976. The expedition led by Prof. Kou KUSUNOKI consisted of 40 members, ten of which constituted the summer party led by the author, deputy leader of the expedition. In addition to the expedition personnel, four observers (two ship engineers, a professional cameraman and a geologist from Belgium, Dr. S. WARTEL) joined the summer party. After leaving Fremantle on December 16, 1976, the ship reached the edge of fast ice, approximately 40 nautical miles NNW of Syowa, on December 31, 1976. Although the FUJI could not cut the channel to Syowa Station due to thick fast ice, all of cargo for the wintering party were delivered by helicopters until January 25, 1977. Four vehicles, including a new-type snow vehicle, SM 50, were immediatly assembled and a new building for ionospheric observations was also constructed. On February 1, 1977 the wintering members of JARE-18 took over duties at the Station. Scientific programs on board the FUJI were largely the continuations from previous years: Oceanographic and biological observations, and the measurement of HF radio wave intensities were carried out throughout the voyage, and aerosol measurements were made from Tokyo to the edge of fast ice near Lutzow-Holm Bay. Several field research parties were sent to exposed rocks and saline lakes along the coast of Lutzow-Holm Bay to make geological, geochemical and ground surveys. A return trip to the inland Mizuho Camp was also carried out. The inland party built an unmanned station for upper atmospheric and meteorological observations at the middle point (69°47'S, 41°34'E, 1,470 m in altitude) between Syowa and the Mizuho Camp. Duties at the Mizuho Camp were taken over by four men of JARE-18 on January 27, 1977. As one of the IMS projects, the ...